Comparison of intrinsic foot muscle function in patients with different lower extremity conditions - Abbis Jaffri; Joseph Park; Joe Hart; Jay Hertel; Susan Saliba (PLoS ONE, 2025)
Background The intrinsic foot muscles (IFM), or foot core, provides stability to the foot skeleton. IFM dysfunction has been linked to foot and ankle injuries; however, the functional assessment of IFM in lower extremity conditions remains a clinical conundrum. We undertook a large study to understand the differences in muscle size and quality of IFM across a spectrum of conditions including Chronic Ankle Instability (CAI), Patellofemoral Pain (PFP), 1st Metatarsophalangeal Joint (1st MTPJ)  arthrodesis and in patients with diabetes. This study compares IFM morphology and tissue quality in patients across these conditions and healthy control group individuals. Methods This study included 119 participants: 35 PFP, 29 CAI, 8 with 1st MTPJ arthrodesis, 9 with Diabetes, and 38 healthy controls. Ultrasound imaging (USI) assessed cross-sectional area (CSA) for muscle size and echogenicity for muscle quality in the Abductor Hallucis (AbH) and Flexor Digitorum Brevis (FDB). All size measures were normalized to body mass. Analysis of Coavariance (ANCOVA) was performed between groups, controlling for age and sex, to identify differences. Results Significant differences (P < 0.05) in the CSA of the AbH were found between all pathology groups and healthy control group, except for the 1st MTPJ group. CSA of FDB showed significant differences (P < 0.01) in all groups except the PFP and 1st MTPJ groups. For echogenicity, significant differences (P < 0.05) were found between groups for both AbH and FDB, while CAI, 1st MTPJ, and PFP groups showed higher FDB echogenicity. Large effect sizes were found for CSA and echogenicity in all groups except PFP. Conclusion This is the first study to our knowledge to collectively analyze multiple clinical groups with suspected IFM weakness in functional position for both muscle size and quality. Significant changes in muscle size and quality were observed, suggesting that clinicians should assess and target IFM rehabilitation to improve foot and ankle function in these populations.